Serum biochemical profile of repeat breeder crossbred cows - CHANDRAHAR, DEEPAK; TIWARl, R P; AWASTHl, M K; DUTTA, G K (The Indian Journal of Animal Reproduction, 2023)
Glucose. inorganic phosphoru s, total protein. albumin , cholesterol and alkaline phosphatase were estimated in bloodserum of repeat breeder crossbred cows and their levels were compared with that of normal fertile cows. The repeat breeder cows hadsignificantly lower (P < 0.0 I) level of blood glucose and inorganic phosphorus while serum calcium, albumin and alkaline phosphatasewere at significantly higher level (P < 0.01). The difference in total protein and serum cholesterol levels between two groups werenon-significant.
Keywords: Albumin; alkaline phosphatase; cholesterol; inorganic phosphorus; glucose; repeat breeder crossbred cows